Safety and efficacy of 2‐weekly cabazitaxel in metastatic castration‐resistant prostate cancer. (27th April 2017) - Clément‐Zhao, Alice; Auvray, Marie; Aboudagga, Hail; Blanc‐Durand, Félix; Angelergues, Antoine; Vano, Yann Alexandre; Mercier, Florence; El Awadly, Nader; Verret, Benjamin; Thibault, Constance; Oudard, Stéphane
Abstract : Objectives: To evaluate the safety and efficacy of a 2‐weekly cabazitaxel schedule in patients with metastatic castration‐resistant prostate cancer (mCRPC). Materials and methods: During the period October 2013 to February 2016, 43 patients with mCRPC were treated with cabazitaxel (16 mg/m 2, on days 1 and 15 of a 4‐week cycle) together with prophylactic granulocyte colony‐stimulating factor (G‐CSF). The safety profile and efficacy (prostate‐specific antigen [PSA] response; biological, clinical or radiological progression‐free survival [PFS] and overall survival [OS]) of the treatment were analysed. Results: All patients had received prior docetaxel and 79.1% abiraterone acetate. At inclusion, 46.5% were aged >70 years and 27.9% had an Eastern Cooperative Oncology Group performance status ≥2. Six patients stopped treatment because of toxicity. Grade ≥3 toxicities were: asthenia (16.3%); neutropenia (11.6%); thrombocytopenia (9.3%); diarrhoea (7%), anaemia (4.7%), febrile neutropenia (4.7%) and haematuria (2.3%). In all, 52.4% achieved a ≥30% PSA response and 40.5% had a ≥50% PSA response. The median OS was 15.2 months. Conclusion: This prospective pilot study suggests that cabazitaxel 16 mg/m² given 2‐weekly has a manageable toxicity profile in docetaxel‐ and abiraterone acetate‐pretreated patients with mCRPC. A prospective phase III trial comparing this regimen with the standard cabazitaxel regimen is planned to confirm these results.